Antlerogenic stem cells extract accelerate chronic wound healing: a preliminary study - Janusz Kmiecik; Michał Jerzy Kulus; Jarosław Popiel; Agnieszka Cekiera; Marek Cegielski (BMC, 2021)
Abstract Background Chronic wounds constitute a significant medical and social problem. Chronic wound treatment may be supported by various techniques, such as negative pressure therapy, phototherapy or stem cells therapy, yet most of those supporting therapies need more evidence to be used for standard wound care. Current study covers the use of sonicated Antlerogenic Stem Cells (ASC) extract on chronic wounds. Methods Study was performed on 20 dermatological patients with venous leg ulcers, divided into two groups - treated with and without ASC extract respectively. The area and circumference of the wounds during the follow-up visits were measured on the wound imprint. Dynamics of wound healing was determined and compared between control and study group; statistics includes changes in absolute values (wound area, circumference), as well as relative (percentage of wound decrease, circumference/area ratio) and their change in time. For the purpose of Ki-67 immunohistochemical staining, sections were sampled from the wound edge at distinct check-points during therapy. Results of both groups were compared with Student test or Mann-Whitney test, depending on results distribution. Results Besides Ki-67 expression, all tested wound healing parameters (including relative and absolute wound decrease and changes in circumference/area ratio) were statistically significant more favorable in experimental group. Conclusion ASC extract significantly supported standard chronic wound treatment. Due to small population of study the results should be considered preliminary, yet promising for further research.